KESADARAN HUKUM BERLALU LINTAS BAGI PENGENDARA KENDARAAN BERMOTOR RODA DUA DI KOTA TEMBILAHAN - Edorita, Widia; ', Sariyati; ', Erdianto (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2017)
In Indonesia in general, and in particular Tembilahan City this citizens legal awareness is still very low Tembilahan City, among others part of the society, especially in not obey the traffic rules so that conflicts between the road and the police. It is evident that there are many motorists who do not have a driving license (SIM) or in other words do not complete either of his letters as well as other vehicle equipment. Legal awareness in the City Tembilahan is still lacking, but these rules were made in order to maintain the safety of the community itself.As for the purpose of this thesis is to know the legal awareness of traffic for motorists two wheels at City Tembilahan and to know the efforts made by the Traffic Unit of the Police Resort Indragiri Hilir to increase legal awareness of traffic for riders of two-wheeled vehicle in Tembihalan cityIn writing this essay, the writer used juridical sociological namely a review of secondary data in the form of legislation, as well as the results of the legal scholars, such as books related to the discussion to then proceed with research on primary data.The conclusion that can be obtained from this study is the first, awareness of traffic laws for riders of two-wheel motor vehicles in the city of Tembihalan still lacking, where there is still a lot of traffic violations committed by drivers of two-wheeled vehicles and every year the number of such violations increases .. Second , efforts made by the Resort Police Traffic Unit Indragiri Hilir to raise awareness of traffic laws for riders of two-wheel motor vehicles in the city tembihalan are preventive measures and efforts represif..Saran writer on issues examined are the First, lack of awareness of traffic laws for riders of two-wheel motor vehicles in the city Tembihalan to be addressed by the Resort Police Traffic Unit Indragiri Hilir, City Tembilahan, both with the efforts for the creation of preventive and repressive society orderly traffic. Second, Socialization needs to be done continuously, especially socialization in schools so that people obey the traffic rules. In case of violation by the two-wheeler riders, then tindakanyang diambiloleh sanction police to motorists who commit violations must be firmly in accordance with regulations or laws applicable.Keywords: Legal Awareness - Traffic - Riders Two Wheel Vehicles